Penerapan Strategi Pembelajaran ASICC untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMAN 1 Kediri - Primandiri, Poppy Rahmatika; Rohmania, Qonita Nur; Afifah, Inayah Nur; Santoso, Agus Muji (Cipta Media Harmoni, 2025)
Critical thinking skills are one of the 21st-century skills that students must master. The learning strategies used by teachers still focus on student understanding, so students have not been able to develop their critical thinking skills. Therefore, the application of ASICC learning strategies is needed to improve students' critical thinking skills. The purpose of this study was to determine the ASICC learning strategy to improve the thinking skills of students at SMAN 1 Kediri. The research method is Classroom Action Research (CAR) with 3 cycles. The research instrument is an integrated cognitive test with critical thinking skills assessed by the Zubaidah rubric (2015). The test results were analyzed descriptively. The results of the data analysis showed an increase in critical thinking skills. From the first cycle, 62.5% of students had high critical thinking skills, then the second cycle increased to 75% of students, and as many as 78.13% of students experienced an increase in critical thinking skills in the third cycle. Based on the results of the study, the conclusion in this study is that the application of ASICC learning strategies can improve students' thinking skills.